2016
DOI: 10.1007/s12195-016-0449-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Reduced Astrocyte Surface Coverage in Cortical Neuron-Glia Co-cultures on Nanoporous Gold Surfaces

Abstract: Nanoporous gold (np-Au) is a promising multifunctional material for neural electrodes. We have previously shown that np-Au nanotopography reduces astrocyte surface coverage (linked to undesirable gliosis) while maintaining high neuronal coverage in a cortical primary neuron-glia co-culture model as long as two weeks in vitro. Here, we investigate the potential influence of secreted soluble factors from cells grown on np-Au on the cell type-specific surface coverage of cells grown on conventional tissue culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…For pl-Au, the difference was lower at roughly 15%. The general trend of reduced cellular attachment with decreasing ligament width was consistent with what has been observed previously for reduced cell coverage on np-Au surfaces [ 35 ], suggesting that adhesion strength plays a role in cellular spreading.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…For pl-Au, the difference was lower at roughly 15%. The general trend of reduced cellular attachment with decreasing ligament width was consistent with what has been observed previously for reduced cell coverage on np-Au surfaces [ 35 ], suggesting that adhesion strength plays a role in cellular spreading.…”
Section: Resultssupporting
confidence: 89%
“…While we attributed the differences in astrocyte detachment (adhesion strength) mainly to the substrate nanotopography, it is important to mention that other factors such as surface chemistry and mechanical stiffness can play an important role in dictating cellular adhesion strength [ 39 ]. In addition, as described in our previous study, for short incubation durations, the probability of cells forming focal adhesion to a pitted surface upon reaching the surface may play a role [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local processes at the surface of the pores or at their interface with a fluid are exploited for applications in fields such as catalysis, [11,[47][48][49][50] sensing, [11,51,52] actuation (see below), optical switching, [140][141][142] electropumping for microfluidic devices, [143] integrated circuit contacting, [144] biological implants, [145][146][147][148] and as electrodes where a large surface area is needed. Local processes at the surface of the pores or at their interface with a fluid are exploited for applications in fields such as catalysis, [11,[47][48][49][50] sensing, [11,51,52] actuation (see below), optical switching, [140][141][142] electropumping for microfluidic devices, [143] integrated circuit contacting, [144] biological implants, [145][146][147][148] and as electrodes where a large surface area is needed.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Nanoporous gold surfaces seeded with both astrocytes and neurons show selective reduction of astrocytic coverage while maintaining high neuronal coverage [Chapman et al, 2015]. This response was later revealed to be due to both an initial inhibition of astrocyte attachment and topographical cues provided by the nanoporous gold structure [Chapman et al, 2016]. Nanoporous alumina surfaces have also been studied, and it was found that pore size was important for astrocyte attachment, focal adhesions, and GFAP expression [Ganguly et al, 2018].…”
Section: Introductionmentioning
confidence: 99%